2003
DOI: 10.1038/nn1008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cortical change across the human life span

Abstract: We used magnetic resonance imaging and cortical matching algorithms to map gray matter density (GMD) in 176 normal individuals ranging in age from 7 to 87 years. We found a significant, nonlinear decline in GMD with age, which was most rapid between 7 and about 60 years, over dorsal frontal and parietal association cortices on both the lateral and interhemispheric surfaces. Age effects were inverted in the left posterior temporal region, where GMD gain continued up to age 30 and then rapidly declined. The traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

152
1,557
11
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,113 publications
(1,740 citation statements)
references
References 30 publications
152
1,557
11
20
Order By: Relevance
“…Of note, T1w scans flagged by a combination of FD¯ and QC ratings: (1) increased with increasing age, and (2) exhibited considerably reduced global and regional estimates of gray matter volume and thickness. Reductions in gray matter volume and thickness are well documented as a hallmark of healthy aging and cognitive decline [DeKosky and Scheff, 1990; Dickerson et al, 2008, 2012; Sowell et al, 2003]. We suggest that these effects may in some cases be overestimated, particularly in certain brain locations, by the inclusion of biased estimates from T1w structural scans with motion artifacts.…”
Section: Discussionmentioning
confidence: 79%
“…Of note, T1w scans flagged by a combination of FD¯ and QC ratings: (1) increased with increasing age, and (2) exhibited considerably reduced global and regional estimates of gray matter volume and thickness. Reductions in gray matter volume and thickness are well documented as a hallmark of healthy aging and cognitive decline [DeKosky and Scheff, 1990; Dickerson et al, 2008, 2012; Sowell et al, 2003]. We suggest that these effects may in some cases be overestimated, particularly in certain brain locations, by the inclusion of biased estimates from T1w structural scans with motion artifacts.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, all the participants in the group of older adults were at least 70 years of age. Therefore, first signs of senescent reductions in neuronal mass (Sowell et al, 2003), and in neurotransmitter availability are likely (Backman and Farde, 2005;Backman et al, 2006;Li et al, 2001), even in early visual processing areas, which are known to be well preserved in aging (Raz et al, 2005). Furthermore, It has been shown that gamma-band activity is modulated by genetic polymorphisms (Demiralp et al, 2007) and psychiatric disorders (Gallinat et al, 2004;Herrmann and Demiralp, 2005) affecting dopaminergic neu-romodulation.…”
Section: Evoked Gamma-band Responses Of Early Visual Processing In Olmentioning
confidence: 99%
“…During child development and aging, the structure and function of the human brain undergo major changes (Sowell et al, 2003;Raz et al, 2005; for reviews, see Baltes et al, 2006;Cabeza et al, 2005;Li, 2003;Lindenberger et al, 2006). Results from post-mortem studies of the brain, magnetic resonance imaging (MRI), functional MRI, as well as electrophysiological studies indicate that human brain development can be characterized as non-linear and heterochronous, with different parts of the brain follow different developmental time courses (Gogtay et al, 2004;Sowell et al, 2003;Thatcher, 1992;Thatcher et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations